1997
DOI: 10.1098/rstb.1997.0120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of innate resistance toToxoplasma gondiiinfection

Abstract: The interaction of protozoan parasites with innate host defences is critical in determining the character of the subsequent infection. The initial steps in the encounter of Toxoplasma gondii with the vertebrate immune system provide a striking example of this important aspect of the host^parasite relationship. In immunocompetent individuals this intracellular protozoan produces an asymptomatic chronic infection as part of its strategy for transmission. Nevertheless, T. gondii is inherently a highly virulent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 50 publications
0
43
0
2
Order By: Relevance
“…Accordingly, Wei et al (Wei et al, 2002) have demonstrated that T.-gondii-infected dendritic cells are resistant to apoptosis but trigger a contactdependent apoptosis in cytotoxic T cells. Modulation of the balance between apoptosis and necrosis at a site of tissue infection could modulate the inflammatory response, thereby promoting either growth as a tachyzoite or triggering stage conversion to the long-term bradyzoite form associated with chronic infection (Alexander et al, 1997;Yap and Sher, 1999). This conversion is crucial for the long-term survival of T. gondii within the host as it mounts an effective immune response against it (Alexander et al, 1997;Yap and Sher, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Wei et al (Wei et al, 2002) have demonstrated that T.-gondii-infected dendritic cells are resistant to apoptosis but trigger a contactdependent apoptosis in cytotoxic T cells. Modulation of the balance between apoptosis and necrosis at a site of tissue infection could modulate the inflammatory response, thereby promoting either growth as a tachyzoite or triggering stage conversion to the long-term bradyzoite form associated with chronic infection (Alexander et al, 1997;Yap and Sher, 1999). This conversion is crucial for the long-term survival of T. gondii within the host as it mounts an effective immune response against it (Alexander et al, 1997;Yap and Sher, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of the balance between apoptosis and necrosis at a site of tissue infection could modulate the inflammatory response, thereby promoting either growth as a tachyzoite or triggering stage conversion to the long-term bradyzoite form associated with chronic infection (Alexander et al, 1997;Yap and Sher, 1999). This conversion is crucial for the long-term survival of T. gondii within the host as it mounts an effective immune response against it (Alexander et al, 1997;Yap and Sher, 1999). Bradyzoites possess considerably lowered metabolic activity and persist for long periods of time (years to decades), with their intracellular localization affording them protection from immune attack (Dubey, 1998;Dubey et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are essential to control infection (11)(12)(13). The tachyzoite form of the parasite invades a variety of cells, where it resides within a specialized parasitophorous vacuole that is created during initial parasite entry into the host cell.…”
Section: Acrophages (M)mentioning
confidence: 99%
“…tion, primarily via dendritic cell activation (6,8,9). However, the mechanism by which infected cells activate and recruit dendritic cells remain unclear but presumably requires synthesis of C-C chemokines that bind and activate the C-C chemokine receptor, CCR5 (10).…”
mentioning
confidence: 99%